Mobile Applications Supporting Oral Self-Care in Orthodontic Patients: A Systematic Review - Hannuksela, Iida (My University, 2026)
Background: Orthodontic treatment, especially with fixed appliances, place special demands on oral hygiene by increasing plaque retention and complicating cleaning of the tooth surfaces, thereby increasing the risk of gingivitis as well as development of white-spot lesions that may even progress into cavitated caries lesions. Objectives: The purpose of this study was to systematically collect and analyze published data on the use and usefulness of digital technology in guiding oral self-care among orthodontic patients, aiming at exploring its influence on patient health behavior and oral health. Search methods: A systematic search for existing literature was performed on electronic databases including PubMed, Web of Science and Scopus. Additionally, the reference lists of the included original articles and relevant reviews were examined to identify potentially relevant studies. Selection criteria: Randomized clinical trials and clinical cohort and follow-up studies as well as systematic reviews were included, provided they focused on orthodontic patients with use of digital technology in supporting their oral hygiene, and articles were published in English language in peer-reviewed journals between 2007 and January 2026. Data collection and analysis: A total 734 records were identified. After selection 27 full texts were assessed, and 16 studies were included. Of the included studies, 12 were clinical studies and four were systematic reviews. Risk of bias was assessed, as applicable, using CASP (Cross Sectional Studies Checklist) and AMSTAR2 (Assessing the Methodological Quality of Systematic Reviews). Results: Altogether, the included 16 studies were on eight different mobile applications, some generally available and some designed for study purposes. The results indicated that mobile applications significantly improved patients’ oral hygiene routines, reduced plaque accumulation and gingival bleeding, and increased patients’ motivation. The overall user experience was predominantly positive, with most participants rating the applications beneficial and recommending their use. Conclusion: Mobile applications and artificial intelligence can serve as valuable tools in supporting oral self-care among orthodontic patients. Further development and integration of these technologies into orthodontic treatment pathways should be encouraged to fully utilize their benefits in patient care.

Tausta: Oikomishoito, erityisesti kiinteillä kojeilla toteutettuna, vaikeuttaa hampaiden puhdistusta ja asettaa siten erityisiä vaatimuksia suuhygienialle. Plakin kertyminen oikomiskojeisiin lisää muun muassa ientulehduksen ja kiilteen demineralisaatiovaurioiden riskiä. Heikko suuhygienia oikomishoidon aikana voi edellä mainittujen riskitekijöiden vuoksi johtaa oikomishoidon keskeyttämiseen ja siten heikompiin hoitotuloksiin. Omahoidon ohjaukseen on tämän vuoksi panostettava, ja sen tueksi saataville on tullut esimerkiksi motivoivia mobiilisovelluksia. Tavoitteet: Tämän tutkimuksen tarkoituksena oli systemaattisesti kerätä ja analysoida julkaistua tietoa digitaalisen teknologian käytöstä oikomispotilaiden suun omahoidon ohjauksessa sekä selvittää sen vaikutusta potilaiden terveyskäyttäytymiseen ja suun terveyteen. Hakumenetelmät: Systemaattinen kirjallisuushaku toteutettiin sähköisissä tietokannoissa PubMed, Web of Science ja Scopus. Lisäksi mukaan otettujen alkuperäisartikkeleiden ja aiheeseen liittyvien katsausten lähdeluettelot käytiin läpi mahdollisesti relevanttien tutkimusten tunnistamiseksi. Valintakriteerit: Mukaan otettiin satunnaistetut kliiniset tutkimukset, kliiniset kohortti- ja seurantatutkimukset sekä systemaattiset katsaukset, edellyttäen että ne käsittelivät oikomispotilaita ja digitaalisen teknologian käyttöä suuhygienian ylläpitämisen tukena. Artikkelien tuli olla julkaistu englanniksi vertaisarvioiduissa lehdissä vuosien 2007 ja tammikuun 2026 välillä. Aineiston keruu ja analyysi: Hakulausekkeilla saatiin eri tietokannoista yhteensä 734 hakutulosta. Valintaprosessin jälkeen arvioitiin 27 kokotekstiartikkelia, joista 16 sisällytettiin analyysiin. Näistä 12 perustui kliinisiin tutkimuksiin ja neljä oli systemaattisia katsauksia. Harhan riskiä arvioitiin soveltuvin osin käyttäen CASP-työkalua (Cross Sectional Studies Checklist) ja AMSTAR2-menetelmää (Assessing the Methodological Quality of Systematic Reviews). Tulokset: Mukaan valikoituneet artikkelit käsittelivät yhteensä kahdeksaa eri mobiilisovellusta, joista osa oli yleisesti saatavilla ja osa suunniteltu tutkimuskäyttöön. Tulokset osoittivat, että mobiilisovellukset paransivat merkittävästi potilaiden suuhygieniarutiineja ja suun omahoidon motivaatiota ja niitä käyttävillä oli vähemmän plakkia ja ienverenvuotoa. Kokonaisuudessaan käyttäjäkokemus oli pääosin myönteinen, ja suurin osa osallistujista piti sovelluksia hyödyllisinä ja suosittelisi niiden käyttöä. Johtopäätökset: Mobiilisovellukset ja tekoäly voivat toimia arvokkaina välineinä oikomispotilaiden suun omahoidon tukemisessa. Näiden teknologioiden jatkokehitystä ja integrointia oikomishoidon hoitopolkuihin tulisi edistää, jotta niiden hyödyt potilashoidossa voidaan hyödyntää täysimääräisesti.
Keywords: orthodontics; oral hygiene; oral self-care; artificial intelligence; mobile applications